Mastery of Concepts and Creativity of Class iv Students on the Mareial of Force Through learning radec - Meisarah, Epita; Sujana, Atep; Sunaengsih, Cucun (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
This research was conducted to trace the effect of the use of RADEC learning models on mastery of students' concepts and creativity. This is motivated by the low mastery of the concepts and creativity of students who are allegedly due to the inappropriate learning carried out by the teacher. The research method used in this study is pre-experiments with one group pretest-posttest design. Participants in this study were IV grade students consisting of 30 people. Data collection is carried out with a test of mastery of concepts and rubik assessment of student creativity. The results of this study indicate that the use of the RADEC learning model increases the ability to master students concepts significantly and can bring up aspects of students creativity such as compliance with material, creation and innovation, student preparation and how to make their work. Based on the results of the study it can be concluded that the use of the RADEC learning model can overcome the low mastery of students concepts and creativity.